Improving the design of the Government of Mali's social protection program for achieving better child nutrition - CGIAR Research Program on Policies, Institutions, and Markets (2018)
In collaboration with the Government of Mali and and the Institut de Recherche pour le Developpement, a team of IFPRI/PIM researchers conducted an impact evaluation of Mali's cash transfer program "Projet Filets Sociaux (Jigisemejiri)". The recommendations of the evaluation have been used by the Government of Mali to improve the impacts of the program on child nutrition starting in 2019.